An evaluation of the abundance of polycyclic aromatic hydrocarbons in Glacier Bay, Alaska - Keever, Stefanie Elaine (School of Oceanography, University of Washington, 2008)
Polycyclic aromatic hydrocarbons are carcinogenic and mutagenic pollutants that settle in sediments, and disrupt the biology of sealife. This study took sediment samples from Glacier Bay, and measured the amount of PAHs present. Comparison samples from Puget Sound were also analyzed. No PAHs were found in Glacier Bay, while one site in Puget Sound, Pier 61, was heavily contaminated. A follow-up study would analyze Glacier Bay sediments after the cruise ship season had been underway for some months.
Keywords: Polycyclic aromatic hydrocarbons -- Alaska -- Glacier Bay -- analysis; Marine sediments--sampling--Alaska--Glacier Bay; Polychlorinated biphenyls -- Environmental aspects -- Washington (State) -- Puget Sound; Gas chromatography